7 + (0-7) * 2/3 = 7 - 14/3 = (21 - 14) / 3 = 7/3 = 2.3
5x5,150 =$<span>25,750 = Answer</span>
Deductions per dependent $5,150 times 5 in 2010
It’s the first one on the top left corner
Answer: Choice B
![x^{1/8}y^{8}](https://tex.z-dn.net/?f=x%5E%7B1%2F8%7Dy%5E%7B8%7D)
======================================================
Explanation:
The two rules we use are
![(a*b)^c = a^c*b^c](https://tex.z-dn.net/?f=%28a%2Ab%29%5Ec%20%3D%20a%5Ec%2Ab%5Ec)
![(a^b)^c = a^{b*c}](https://tex.z-dn.net/?f=%28a%5Eb%29%5Ec%20%3D%20a%5E%7Bb%2Ac%7D)
When applying the first rule to the expression your teacher gave you, we can say that:
![\left(x^{1/4}y^{16}\right)^{1/2} = \left(x^{1/4}\right)^{1/2}*\left(y^{16}\right)^{1/2}](https://tex.z-dn.net/?f=%5Cleft%28x%5E%7B1%2F4%7Dy%5E%7B16%7D%5Cright%29%5E%7B1%2F2%7D%20%3D%20%5Cleft%28x%5E%7B1%2F4%7D%5Cright%29%5E%7B1%2F2%7D%2A%5Cleft%28y%5E%7B16%7D%5Cright%29%5E%7B1%2F2%7D)
Then applying the second rule lets us say
![\left(x^{1/4}\right)^{1/2}*\left(y^{16}\right)^{1/2} = x^{1/4*1/2}*y^{16*1/2} = x^{1/8}y^{8}](https://tex.z-dn.net/?f=%5Cleft%28x%5E%7B1%2F4%7D%5Cright%29%5E%7B1%2F2%7D%2A%5Cleft%28y%5E%7B16%7D%5Cright%29%5E%7B1%2F2%7D%20%3D%20x%5E%7B1%2F4%2A1%2F2%7D%2Ay%5E%7B16%2A1%2F2%7D%20%3D%20x%5E%7B1%2F8%7Dy%5E%7B8%7D)
Therefore,
![\left(x^{1/4}y^{16}\right)^{1/2} = x^{1/8}y^{8}](https://tex.z-dn.net/?f=%5Cleft%28x%5E%7B1%2F4%7Dy%5E%7B16%7D%5Cright%29%5E%7B1%2F2%7D%20%20%3D%20x%5E%7B1%2F8%7Dy%5E%7B8%7D)
-------------
In short, we just multiplied each exponent inside by the outer exponent 1/2.
So that explains why the exponents go from {1/4,16} to {1/8,8} for x and y in that exact order.
Think through this one...
9:48 + 9 minutes = 9:57
9:57 + 30 minutes = 10:27
10:27 + 3 hours = 1:27 p.m.